Emotion regulation-related processes and shame and their relationship with depression, anxiety and stress symptoms in people facing psoriasis - Galhardo, Ana (2022)
The current study sought out to examine the associations between sociodemographic and clinical variables, shame, emotion regulation-related processes (cognitive fusion, experiential avoidance, self-compassion and self-judgement), and symptoms of depression, anxiety, and stress in people with a psoriasis diagnosis. One hundred and forty-eight patients (112 females and 36 males) were recruited through the Associação Portuguesa da Psoríase (Portuguese psoriasis patients’ association). Participants completed online measures of negative emotional symptoms (depression, anxiety and stress), chronic illness-related shame, chronic illness-related cognitive fusion, experiential avoidance, self-compassion, and self-judgment. Three-stage hierarchical multiple regression analyses were conducted with depressive, anxiety, and stress symptoms as the dependent variables. Experiential avoidance, self-judgment and years of education were associated with depression, anxiety, and stress symptoms. Chronic illness-related shame was also associated with depressive symptoms in people with psoriasis. Emotion regulation processes and shame should be considered in clinical work with people facing a psoriasis diagnosis. Mindfulness-based programs, Acceptance and Commitment Therapy and Compassion Focused Therapy may be adequate for this population due to their specific target on emotion regulation processes.